The history of ion beam therapy in Germany - Jäkel, Oliver; Kraft, Gerhard; Karger, Christian (Zeitschrift für medizinische Physik, 2022)
The advantageous depth dose profile of ion beams together with state of the art beam delivery and treatment planning systems allow for highly conformal tumor treatments in patients. First treatments date back to 1954 at the Lawrence Berkeley Laboratory (LBL) and in Europe, ion beam therapy started in the mid-1990s at the Paul-Scherrer Institute (PSI) with protons and at the Helmholtz Center for Heavy Ion Research (GSI) with carbon ions, followed by the Heidelberg Ion Therapy Center (HIT) in Heidelberg. This review describes the historical development of ion beam therapy in Germany based on the pioneering work at LBL and in the context of simultaneous developments in other countries as well as recent developments.